2010
DOI: 10.1177/0300985810381907
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Functional Characterization of Pulmonary Bovine Odorant-Binding Protein

Abstract: Bovine odorant-binding protein (OBP) may function in olfaction and defense against oxidative injury, but its role in inflammation and defense against bacterial infection has not been investigated. Expression of OBP was discovered in the bovine lung and found to undergo changes in abundance during glucocorticoid administration and stress. OBP was localized to nasal, tracheal, and bronchial mucosal glands with immunohistochemistry, with faint expression in airway surface epithelium and none in bronchioles or alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In addition, this protein has been related to inflammation, showing a decrease in lungs in bovine after LPS administration. This decrease in OBP levels may be an additional mechanism to allow inflammatory mediators to stimulate neutrophil recruitment and oxidative burst in the lung and possibly in other tissues [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this protein has been related to inflammation, showing a decrease in lungs in bovine after LPS administration. This decrease in OBP levels may be an additional mechanism to allow inflammatory mediators to stimulate neutrophil recruitment and oxidative burst in the lung and possibly in other tissues [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that, when inflammation was detected in VNSE, regardless of the intensity, the expression of OBP in the surrounding areas was increased. This observation could be explained by the modulatory role of OBP in the inflammatory response proposed by Mitchell et al (62), as this protein seems to inhibit neutrophil recruitment by inflammatory mediators in the respiratory system (62). Some studies on other species demonstrated OBP compensatory properties on olfactory systems, where different OBP subtypes have been reported to occur simultaneously (63)(64)(65).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, recent data suggest that OBPs may also act as antimicrobial components against pathogenic microorganisms (Bianchi et al 2019). The dual role of OBPs in olfaction and immunity is also highlighted by a study indicating that OBPs may modulate neutrophil recruitment through binding to macrophage-derived inflammatory mediators in the upper airway (Mitchell et al 2011).…”
Section: Proposed Mechanisms For the Modulation Of Vertebrate Olfactory Epithelium Functionality By The Immune Systemmentioning
confidence: 97%